Effectiveness of Manual Therapies in the Management of Migraine Symptoms: A Narrative Review (International Journal of Physiotherapy, 2025)
Background: Migraine is a prevalent neurological disorder that affects 12–15% of people worldwide and is one of the leading causes of disability. Although pharmacological interventions are available, numerous patients turn to nonpharmacological methods because of side effects and long-term use of medications. Manual therapy has been considered a possible adjunct treatment for the alleviation of symptoms.Methods: A literature review was conducted using databases such as PubMed, Scopus, Cochrane Library, and PEDro, following the PICO framework. The inclusion criteria were English-language randomized controlled trials (RCTs) published between 2015 and 2025 that assessed manual therapy interventions in patients with migraine. Outcomes assessed were headache frequency, pain intensity, disability indices, and quality of life.Result: Results from included RCTs show impressive improvements after manual therapy. Articulatory treatment resulted in decreased migraine frequency (up to 38%) and intensity (up to 47%), along with corresponding improvements in quality of life and reduced medication use. Craniosacral therapy also showed statistically significant decreases in headache intensity, frequency, and disability.Conclusion: Manual therapy, especially articulatory and craniosacral manipulation, helps decrease the burden of migraines. Such evidence favors adding manual therapy as part of the multidisciplinary approach to treating migraines but calls for larger studies with uniform protocols and more extended follow-up periods.